VLOG-BASED BASIC TECHNIQUES LEARNING BASIC ENGINEERING BACKGROUND SERVICES TO INCREASE STUDENTS' LEARNING INTEREST AT SMP NU TERPADU BREBES - zaini nadhif (STKIP Muhammadiyah Kuningan, 2023)
The purpose of this research and development is to develop teaching materials and teaching media based on vlogs, as well as, to determine student learning responses to the development of teaching materials and learning media based on Vlogs for class VIII SMP NU Terpadu Kab. BREBES. This study uses the Research & Development Research & Development method from Borg and Gall which consists of 8 stages, namely 1) Research and data collection stages, 2) Planning stages, 3) Initial product format development stages, 4) Initial trial stages by validators, 5 ) Stages of product revision, 6) Stages of field trials, 7) Stages of product revision II, 8) Stages of dissemination and implementation. The research subjects were lecturers, teachers and students of Junior High School NU Terpadu Kab. BREBES . Collecting data using data using questionnaires, interview guidelines and observation sheets. The results of this development research are 1) It has succeeded in developing vlog-based teaching materials and teaching media, 2) This development product has been proven valid based on the results of the questionnaire obtained from the validator's responses, 88% of teaching materials designer experts with the